2003
DOI: 10.1021/ic026141e
|View full text |Cite
|
Sign up to set email alerts
|

51V Solid-State Magic Angle Spinning NMR Spectroscopy and DFT Studies of Oxovanadium(V) Complexes Mimicking the Active Site of Vanadium Haloperoxidases

Abstract: A series of 11 oxovanadium(V) complexes mimicking the active site of vanadium haloperoxidases have been investigated by (51)V magic angle spinning NMR spectroscopy and density functional theory (DFT). The MAS spectra are dominated by the anisotropic quadrupolar and chemical shielding interactions; for these compounds, C(Q) ranges from 3 to 8 MHz, and delta(sigma) is in the range 340-730 ppm. The quadrupolar coupling and chemical shielding tensors as well as their relative orientations have been determined by n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
126
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 87 publications
(137 citation statements)
references
References 72 publications
10
126
1
Order By: Relevance
“…Note that δ 11 has a deviation within experimental error, δ 22 deviates by 100 to 150 ppm, while δ 33 deviates by 330 to 430 ppm. Previously, quantum chemical calculations of the chemical shift anisotropy of vanadium coordination complexes have shown good agreement with experiment for complexes with O and N coordinated to the V. 26 The orientation of the tensors in the molecular frame, which is not available from the NMR experiments, has also been obtained from the calculations. However, given the errors in the EFG asymmetry parameter the reliability of the EFG orientation obtained from the calculations is questionable.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 73%
See 4 more Smart Citations
“…Note that δ 11 has a deviation within experimental error, δ 22 deviates by 100 to 150 ppm, while δ 33 deviates by 330 to 430 ppm. Previously, quantum chemical calculations of the chemical shift anisotropy of vanadium coordination complexes have shown good agreement with experiment for complexes with O and N coordinated to the V. 26 The orientation of the tensors in the molecular frame, which is not available from the NMR experiments, has also been obtained from the calculations. However, given the errors in the EFG asymmetry parameter the reliability of the EFG orientation obtained from the calculations is questionable.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 73%
“…Furthermore, the solution 51 V NMR studies of these compounds demonstrated that the isotropic chemical shifts change upon modification of the hydroxylamido ligand, whereas only small changes were observed when the dipicolinate group was functionalized. However, knowledge of the isotropic chemical shifts in solution are insufficient for deriving information about the three-dimensional electronic and geometric structure of the vanadium site, 20,26 and therefore the anisotropic EFG and chemical shift tensor parameters measured here by SSNMR and calculated using DFT are important.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations